CALENGSAI : KREATIVITAS DAN INOVASI PEKERJA SENI DALAM MEMPERTAHANKAN KESENIAN TRADISIONAL - Dyah Tjaturrini (Jurnal Lingua Idea, 2018)
Calung Lengger is one of the traditional art from Banyumas, Central Java. Calung Lengger is a tool / media to represent the identity of Banyumas community. Calung Lengger experiencing ups and downs in its development, caused by the progress of science and technology. This influence is very large for the development of the traditional arts of calung and lengger. This traditional art of calung lengger must be defended in order to maintain the existence of art itself. Various efforts are made by art workers by innovation and creation. This innovation and creations by incorporating other traditional arts such as lion dance, art from Tiongkok. This can happen because of the intensive interaction by using the symbols that exist in each art. Symbolic interaction is a continuous relationship between symbols and intercations. The symbol used is a representation of a mutually agreed phenomenon. The interaction between Banyumas and Tionghoa community is bridged by symbols, and the symbol is a verbal symbol that uses art as a means of representing a phenomenon. This intensive interaction also results in a combination of two cultures that occur in a harmonious and peaceful life.